Prospective Study on Group of Heart Failure Patients in Ibn Al-Bitar Center for Cardiac Surgery for Evaluation of CRT-D Effect - Mais O. Al-Saffar; Rafid B. Al-Taweel; Zaid Al-Dahhan; Khalil Sarhan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The main objective of this study was to assess the effect of CRT-D device on the cardiacmechanics for group of patients with end-stage heart failure (HF).Methods: For 13 patients with heart disease who are supposed to undergo a CRT (Cardiac ResynchronizationTherapy) implant, a single center study has been performed at the Ibn Al-Bitar center for cardiac surgery.End stage HF (heart failure) with (NYHA class III or IV) left ventricular ejection fraction < 35% and QRSinterval >120 ms were selected for CRT. Before CRT implantation, the clinical evaluation was measured and2-D echocardiography was performed to measure left ventricular volume and ejection fraction. Combiningboth M-mode echocardiography, TDI color-coded tissue and speckle tracking technique, left ventriculardesynchrony has been tested. Clinical condition and increase in echocardiographic parameters (leftventricular ejection fraction and volume) were re-assessed after 3 months of follow-up.Results: Post CRT-D implantation, significant clinical improvement was observed in 54% of the patients.Class of functional capacity decreased in the third month after implantation compared to basal levels (P <0.01). Left ventricular end-diastolic (LVIDd) and end-systolic diameters (LVIDs) decreased, and LV systolicfunction improved significantly at the 3rd month after implantation when compared to baseline values.Decrease in LV volumes continued to the 3rd month, that the decrease in LVESV was statistically significant(P = 0.07), reduction in end-diastolic volume was also statistically significant (P = 0.07). Ejection fractionand fractional shortening showed insignificant (p > 0.05) increase after CRT-D implantation.Discussion: Patients were divided into responders and non-responders, based on improvement in NYHAfunctional class, it became evident that an improvement in clinical parameters was observed only in theresponders. Moreover, improvements in LVEF and reverse remodeling were also observed only in theresponders. Conclusion: Cardiac resynchronization therapy is considered as a therapy for patients with severe heartfailure, with statistically significantly improve in clinical and echocardiographic parameters.